2021
DOI: 10.1186/s12935-021-01753-x
|View full text |Cite
|
Sign up to set email alerts
|

CircTP63 promotes hepatocellular carcinoma progression by sponging miR-155-5p and upregulating ZBTB18

Abstract: Background Hepatocellular carcinoma (HCC) is the leading cause of tumor-related death worldwide due to high morbidity and mortality, yet lacking effective biomarkers and therapies. Circular RNAs (circRNAs) are a group of non-coding RNAs that regulate gene expression through interacting with miRNAs, implicating in the tumorigenesis and progression. A novel circRNA, circTP63, was reported to be an oncogene in HCC. However, its role in HCC remains unclear. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Another study shows that circular RNA circTP63 enhances estrogen receptor-positive breast cancer progression and malignant behaviors through the miR-873-3p/FOXM1 axis [ 13 ]. In hepatocellular carcinoma (HCC), circTP63 is significantly upregulated in HCC tissues and cell lines, and circTP63 overexpression promotes tumor progression by sponging miR-155-5p and upregulating ZBTB18 expression [ 14 ]. However, its role in GBC progression remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Another study shows that circular RNA circTP63 enhances estrogen receptor-positive breast cancer progression and malignant behaviors through the miR-873-3p/FOXM1 axis [ 13 ]. In hepatocellular carcinoma (HCC), circTP63 is significantly upregulated in HCC tissues and cell lines, and circTP63 overexpression promotes tumor progression by sponging miR-155-5p and upregulating ZBTB18 expression [ 14 ]. However, its role in GBC progression remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In HCC-related studies, circTP63 was found to be upregulated in HCC, and was considered to be a tumor promoter to accelerate HCC proliferation and metastasis via the miR-155-5p/ZBTB18 network. 21 On the contrary, Ma et al reported that circ_0014717 was downregulated in HCC, which could suppress HCC growth and metastasis by reducing BTG2 through sponging miR-668-3p. 22 Here, we screened a new circRNA, circANTXR1.…”
Section: Discussionmentioning
confidence: 99%
“…CircEPB41L2 exerted a carcinogenic role in HCC through interacting directly with miR-590-5p [ 22 ]. CircTP63 was conspicuously enhanced in HCC tissues and cells and accelerated HCC progression via miR-155-5p/ZBTB18 regulatory network [ 23 ]. The analysis of GSE94508 dataset showed circUCK2, a splicing form of UCK2, is highly expressed in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%